PENGENALAN APLIKASI CERDAS CERMAT MUSLIM KEPADA SANTRI TPA AT-TAQWA - Perdana Sari, Yolen; Yanti, Fitri; Sutresna, Jaka (Universitas Pamulang, 2025)
In the era of globalization and the industrial revolution 4.0, technological developments have significantly influenced various aspects of life, including the education sector. Technology enables the creation of new learning methods that are more interactive, engaging, and accessible, including in non-formal education such as the Al-Qur’an Education Park (TPA). TPA At-Taqwa, located in Paradise Serpong City, serves approximately 40 students aged 4–12 years with only two teachers. To enhance the quality of Islamic education in this environment, a community service activity was conducted by lecturers from Universitas Pamulang, introducing the “Cerdas Cermat Muslim” application. This Android-based application offers Islamic educational content such as Akidah Akhlak, Fiqh, Islamic History, and Qur’an in an interactive quiz format tailored for children. Prior to implementation, the team conducted preliminary coordination, technical preparation, and application trials to ensure readiness. The three-day program included lectures, discussions, and hands-on practice. Participants were guided intensively by the facilitators in using the app’s features. The results demonstrated strong enthusiasm from the participants, who successfully operated the application independently and acknowledged its benefits in the learning process. About 98% of participants found the application helpful, and 84% expressed interest in installing it on their personal devices. These findings highlight the high potential of educational applications to improve Islamic learning outcomes in non-formal education settings. Moreover, this activity underlines the role of digital technology as a strategic tool to overcome conventional learning limitations. Keywords: application; Islamic education; TPA; interactive learning; community service